2014
DOI: 10.3174/ajnr.a3846
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Echo-Planar J-Resolved Spectroscopic Imaging in the Human Brain Using Compressed Sensing: A Pilot Validation in Obstructive Sleep Apnea

Abstract: BACKGROUND AND PURPOSE Echo-planar J-resolved spectroscopic imaging is a fast spectroscopic technique to record the biochemical information in multiple regions of the brain, but for clinical applications, time is still a constraint. Investigations of neural injury in obstructive sleep apnea have revealed structural changes in the brain, but determining the neurochemical changes requires more detailed measurements across multiple brain regions, demonstrating a need for faster echo-planar J-resolved spectroscopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 34 publications
3
46
1
Order By: Relevance
“…Previous OSA spectroscopy studies found differences in neurochemical levels, such as decreased N -acetylaspartate (NAA), a neuronal marker, and increased levels of the excitatory neurotransmitter glutamate, in limbic brain regions including the hippocampus, thalamus, and putamen (Sarma et al, 2014, 2016). These findings suggest neural injury and increased excitation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous OSA spectroscopy studies found differences in neurochemical levels, such as decreased N -acetylaspartate (NAA), a neuronal marker, and increased levels of the excitatory neurotransmitter glutamate, in limbic brain regions including the hippocampus, thalamus, and putamen (Sarma et al, 2014, 2016). These findings suggest neural injury and increased excitation.…”
Section: Introductionmentioning
confidence: 99%
“…Participants were instructed to refrain from caffeine and alcohol for 24 h prior to their visit. Metabolites were measured with a novel 2D-magnetic resonance spectroscopy (MRS) method, accelerated 4D echo-planar J-resolved spectroscopic imaging (4D-EP-JRESI) (Sarma et al., 2014). The procedure uses non-uniform undersampling (NUS) for acceleration with compressed sensing reconstruction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This problem can be alleviated and this technique may potentially be extended to spectroscopic imaging by the synergy of modern techniques and technology, such as high field scanners (>3 T) [82], parallel imaging (e.g., SENSE [83,84] and GRAPPA [85,86]) with multichannel coils, fast acquisition sequences (e.g., EPSI [86,87], spiral acquisition [88]), and compressed sensing (allowing several-fold acceleration by randomly skipping some t 1 steps [89]). This approach is very similar to that used for echo-planar J-resolved MRSI using compressed sensing [90].…”
Section: Theoretical Modeling Of the Mrs Signal With Sideband Artifactsmentioning
confidence: 94%
“…The need for determining the neurochemical changes across multiple brain regions in patients with CNS disorders in a clinically viable timeframe has led to developmental of faster 4D echo-planar J-resolved spectroscopic imaging techniques, which combine the advantages of 2D MR spectroscopic imaging and echo-planar spectroscopic imaging. Sarma et al 15 demonstrated 4D echo-planar J-resolved spectroscopic imaging by using the nonuniform undersamplingbased acquisition and compressed sensing reconstruction and showed it to be a clinically viable imaging technique in patients with obstructive sleep apnea. The study highlights the clinical applicability of their methodology, which could detect additional neurochemical changes in patients with obstructive sleep apnea previously reported by 1D MR spectroscopy.…”
mentioning
confidence: 99%